Dolly Parton [compact disc, unabridged] : songteller, my life in lyrics - Parton, Dolly; Oermann, Robert K. (Recorded Books, Inc., 2020)
Mining over sixty years of songwriting, Dolly Parton highlights her music and brings listeners behind the lyrics by exploring the songs that have defined her journey.